Active deformation delineated by geomorphic and sedimentary response of rivers, central Zagros fold – thrust belt, SW iran - Hakimeh Amanipoor (Geodesy and Cartography, 2015)
The mountain generation in Iran is because of continental collision between the Arabian and Eur-asia plate. Southwestern Iran shows active shorten that its evidences is deformation of crust and frequent earthquakes. At depth, active basement of the Zagros fold-thrust-belt in southwestern Iran, which are covered by folding of the Phanerozoic sediments, affected by some blind thrusted faults that have seismic nature.